Static Chamber Measurements of Ammonia Volatilization from Manured Soils: Impact of Deployment Duration and Manure Characteristics. Issue 1 (31st December 2014) - Miola, Ezequiel C.C.; Aita, Celso; Rochette, Philippe; Chantigny, Martin H.; Angers, Denis A.; Bertrand, Normand; Gasser, Marc-Olivier
Abstract : Static chambers (SC) are a simple low‐cost option for measuring NH3 volatilization from agricultural soils. However, it is uncertain how their estimates relate to more sophisticated methods. In this study, we compared SCs and wind tunnels (WT) for the field measurement of NH3 volatilization during 22 d following surface application of seven solid poultry manures to a bare agricultural soil. Our objective was to determine the impact of SC deployment duration and manure characteristics on the emission estimates. Total NH3 losses measured using SCs were on average 23% lower than using WTs. This bias varied with deployment time as the SC/WT emission ratio increased from a value of 0.2 immediately following deployment to a plateau of 1.6, 8 d later. The performance of SCs was also influenced by manure type, with the SC/WT ratio ranging from 0.40 to 1.30 after 22 d. Globally we found that (i) shortly after deployment, absence of air movement inside SCs results in an underestimation of soil‐surface NH3 volatilization (≈80%) compared with WT; (ii) this initial bias appears independent of the NH3 source intensity; (iii) the underestimation decreases with deployment duration; and (iv) the cumulative bias after 22 d is impacted by the modified transformations of manure organic N (MON) inside SCs. We conclude that SCs yield biased absolute estimates of NH3 volatilization rates in most situations. Furthermore, their use for comparing relative emission potential between various surface‐applied solid manures is also limited to periods during which the transformation of the manure N is not affected by SC deployment.